Incidence of ascites on broilers fed with high energy level commercial rations - Neto, M. G. (2002)
An experiment was carried out to verify the effects of different commercial rations with high energy level on the incidence of ascites on broilers. A total of 1,200 Hubbard birds were housed in 12 boxes, in a complete random design with four treatments and three replications of 100 birds in each replication. Treatments consisted of three commercial crumbled pellets diets (B, C and D), which were compared to the control (A), an initial mash diet, from up one to 39 days of broilers age. There was no significant difference between the treatments for feed consumed, body weight, and body gain of the birds, But, the feed conversion of the treatment C showed significantly better results. However, it was observed that this same treatment had the highest value of mortality and such high mortality percentage was caused by ascites. The results showed that the conversion feed was a very important factor on the incidence of ascites.